Possible hormonal biomarkers in the diagnosis of overtraining syndrome (OTS) - a literature review - Nowicka, Iga; Łuniewski, Bartosz; Macko, Angelika; Łuniewska, Maria; Rios Turek, Paweł (Quality in Sport, 2026)
Background: Physical activity is important for prevention of some of the most common diseases worldwide: cardiovascular disease, type 2 diabetes mellitus, and certain types of cancers. However, extremely strenuous exercise performed over a prolonged period can lead to Overtraining Syndrome (OTS), especially in athletes competing at elite levels. This is characterized by psychological, neuroendocrine and immunological disturbance, and a prolonged decrease in exercise tolerability. Although many theories have emerged about the etiology of this condition, the pathophysiology is still unknown. That makes it difficult to diagnose OTS, as the resulting symptoms, including fatigue and diminished exercise performance, are common in athletes and largely nonspecific. Aim: The goal of this study was to synthesize current evidence on possible hormonal biomarkers that may assist in the diagnosis of OTS. Materials and methods: The search was conducted via PubMed, Science Direct, NCBI, and Google Scholar databases for articles with a focus on human studies. The keywords included “overtraining syndrome”, “OTS”, “overreaching syndrome”, “hormonal biomarkers”, “testosterone cortisol ratio”, “testosterone estradiol ratio”, “hypothalamic pituitary axis”, “hypothalamic dysfunction”, “EROS-HPA axis”. Results: Certain studies suggest that basal and dynamic hormone measurements may aid in the diagnosis of OTS. The Cadegiani and Kater EROS studies (2017-2020) [9, 10, 11] have proposed diagnostic tools composed of clinical and biological markers that, in the tested cohort, showed 100% diagnostic accuracy in distinguishing between OTS and non-OTS athletes. However, without an established pathophysiological pathway, many researchers remain sceptical. Conclusions: There is a definite need for validation of proposed diagnostic tools and reaching a consensus on the diagnostic process of OTS, instead of having it be a diagnosis of exclusion.